Speech event analysis of President Prabowo’s statement on the August 2025 protests - Nabila Noor Adelin Afini; Cynara Cleva Cesimira; Apulia Charis Ariefah; Teguh Sarosa (Journal Albion : Journal of English Literature, Language, and Culture, 2026)
This study analyzes President Prabowo Subianto’s speeches delivered in response to the August 2025 demonstrations in Indonesia using Dell Hymes’s SPEAKING framework. The background of this research arises from the growing importance of speech event analysis in understanding how political leaders communicate during social crises. The study aims to identify how each SPEAKING component appears in Prabowo’s statements and how these speech events illustrate the communicative function of language amid public unrest. Employing a qualitative descriptive method, the data were drawn from official video recordings and verified transcripts, then coded and interpreted systematically. The findings show that Prabowo’s speeches apply structured participation, directive and commissive acts, and deliberate keying to calm the public, legitimize state authority, and distinguish peaceful aspirations from unlawful behavior. This research demonstrates the role of speech events as social acts that influence public perception, support political stability, and guide crisis communication.